Compositions and articles of improved size radar cover materials
Patent Information
- Application Number
- CN202180069557.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-17
- Filing Date
- 2021-08-17
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2041-08-17
AI Technical Summary
Existing automotive radar dome materials have high loss factors at high-frequency microwave frequencies, resulting in poor transmittance. At the same time, their transmittance is insufficient at laser wavelengths, making it difficult to meet the requirements of advanced driver assistance systems.
It employs a composition containing crystalline or semi-crystalline polyester, amorphous polymer resin and reinforcing filler. By adjusting the proportions and refractive index relationships of each component, the loss factor is reduced and the transmittance is improved, making it suitable for microwave and laser wavelengths.
With a loss factor of less than 0.01 at 77GHz, low warpage, and high laser transmittance, it meets the performance requirements of automotive radomes and is suitable for internal or external components of automotive radar sensors.
Smart Images

Figure BDA0004171161590000051 
Figure BDA0004171161590000061 
Figure BDA0004171161590000081
Abstract
Description
Technical Field
[0001] This disclosure relates to materials exhibiting microwave and light transmission properties, and particularly to materials exhibiting microwave and light transmission properties for use in automotive radar sensor applications. Background of the Invention
[0003] Microwave radiation (ranging from approximately 1 GHz (300 mm wavelength) to 300 GHz (1 mm wavelength)) is the most common electromagnetic energy source used in the operation of radar sensors for automotive applications. Radio detection and ranging (RADAR) is a critical component of automotive sensing systems. Reinforced or filled polybutylene terephthalate (PBT) solutions are widely used as radome materials due to their good balance in mechanical properties, flowability, and chemical resistance. With the development of Advanced Driver Assistance Systems (ADAS), new radio frequencies have been allocated globally. Compared to the conventional 24 GHz frequency, 77 GHz has emerged due to its high resolution, long-range coverage, and high-speed adaptability. There remains a need in the field for filler materials with ideal mechanical properties and suitable for use as internal or external components that transmit MW radiation in automotive radar applications.
[0004] This disclosure addresses these and other needs in various aspects. Summary of the Invention
[0005] Various aspects of this disclosure relate to compositions comprising: (a) about 10% to about 87% by weight of at least one crystalline or semi-crystalline polymer, wherein the at least one crystalline or semi-crystalline polymer comprises a crystalline or semi-crystalline polyester; (b) about 3% to about 40% by weight of an amorphous polymer resin; and (c) about 10% to about 70% by weight of a reinforcing filler, wherein the combined weight percentage of all components does not exceed 100% by weight, and all weight percentages are based on the total weight of the composition. When measured using a refractometer, the refractive index of the at least one crystalline or semi-crystalline polymer may be lower than the refractive index of the reinforcing material, and the refractive index value of the amorphous polymer resin may be greater than the refractive index value of the reinforcing filler. The composition may exhibit a smaller dissipation factor (Df) than that observed in a reference composition in the absence of an amorphous polymer resin.
[0006] As measured according to the disclosed method, this composition exhibits improved warpage compared to a comparative composition that does not contain an amorphous polymer. When measured according to the resonance cavity method, at frequencies of 1–90 GHz with a ratio of ε” to ε’, this composition exhibits a loss factor (Df) of about 0.001 to about 2. Attached Figure Description
[0007] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate several aspects of this disclosure and, together with the specification, serve to explain the principles of this disclosure.
[0008] Figure 1 Table 1-1 shows the formulation of a PBT composition filled with 30% glass.
[0009] Figure 2 Table 1-2 presents the properties of the PBT composition filled with 30% glass.
[0010] Figure 3 presents Figure 1 Figure -3 shows the transmittance of a PBT composition filled with 30% glass from 250 to 2500 nm.
[0011] Figure 4 presents Figure 1 -4 shows the thickness-dependent transmittance plot of a PBT composition filled with 30% glass.
[0012] Figure 5 Table 2-1 shows the formulation of a PBT composition filled with 30% low-dk glass.
[0013] Figure 6 Table 2-2 shows the properties of the PBT composition filled with 30% low dk glass.
[0014] Figure 7 Table 3-1 shows formulations containing a high glass filler ratio.
[0015] Figure 8 Table 3-2 presents the properties of compositions containing a high glass filler ratio.
[0016] Figure 9 Table 4-1 shows formulations containing a lower glass filler ratio.
[0017] Figure 10 Table 4-2 presents the properties of compositions containing a low glass filler ratio.
[0018] Figure 11 Table 5-1 shows the formulations of compositions containing different types of additives and fillers.
[0019] Figure 12 Table 5-2 shows the properties of compositions containing different types of additives and fillers.
[0020] Figure 13 Table 6-1 shows formulations of compositions containing different second polymers.
[0021] Figure 14 Table 6-2 presents the properties of compositions containing different second polymers. Detailed Implementation
[0022] This disclosure relates to filled PBT compositions that can be used as radomes for microwave (MW) transmission purposes. Microwave radiation, ranging from about 1 GHz (300 mm wavelength) to 300 GHz (1 mm wavelength), is the most common electromagnetic energy source used for the operation of automotive radar sensors. This disclosure provides a series of polymer-based materials that improve the performance of filled PBT / glass fiber (GF) resin as radomes.
[0023] Conventional PBT GF materials maintain a loss factor of approximately 0.015 at 77 GHz and can negatively impact high-frequency wave transmission. For radome applications, filled PBT with a loss factor (Df) of less than 0.01 at 77 GHz may be required. Known methods for reducing the Df of PBT may include incorporating low-Df polymeric resins miscible with (or blended with) PBT, such as polypropylene (PP). However, since both PBT and PP are crystalline / semi-crystalline polymers, PBT / PP blends exhibit severe warpage, making them unsuitable for use as housing materials, such as radomes.
[0024] To meet ADAS trends, PBT with both low Df and flatness (low warpage) at 77 GHz is crucial. Furthermore, due to the increasing radar-driven transportation, more efficient means of manufacturing radar equipment housings have been adopted; for example, laser welding, which requires radome materials to allow laser transmission (at wavelengths of 900-1100 nm). This disclosure addresses these needs. The disclosed composition of low-Df PBT exhibits minimal warpage, such as good flatness (characterized by low warpage), and maximum laser transmittance. The disclosed composition combines low-Df, high-RI amorphous resin, PBT, and fillers to provide a useful material for high-quality radomes. In some aspects, the composition may contain recycled materials. This disclosure provides a glass-filled material based on thermoplastic substances that is rigid and has a high modulus, maintains its shape during molding, and is suitable as an internal or external component for transmitting MW radiation in automotive radar applications.
[0025] Before disclosing and describing the compounds, compositions, articles, systems, devices, and / or methods of the present invention, it should be understood that, unless otherwise specified, they are not limited to specific synthetic methods, or, unless otherwise specified, are not limited to specific reagents, and therefore, they are subject to change. It should also be understood that the terminology used herein is for descriptive purposes only and is not intended to be limiting.
[0026] This disclosure covers various combinations of elements of this disclosure, such as combinations of elements from dependent claims that are subordinate to the same independent claim.
[0027] Furthermore, it should be understood that, unless expressly stated otherwise, any method described herein is not intended to be construed as requiring its steps to be performed in a particular order. Therefore, unless a method claim actually describes the order in which its steps are followed, or unless the claims or description specifically state that the steps are limited to a particular order, no inference is intended in any respect of the order. This applies to any possible non-explicit basis of interpretation, including logical questions concerning the arrangement of steps or the flow of operations; simple meanings derived from grammatical organization or punctuation; and the number or type of aspects described in the description.
[0028] Thermoplastic resin composition
[0029] This disclosure relates in various aspects to thermoplastic compositions comprising at least one crystalline or semi-crystalline polyester, an amorphous resin, and reinforcing fillers. In some aspects, the thermoplastic composition may comprise recycled resins or additional components, such as recycled crystalline or semi-crystalline polyesters, recycled amorphous resins, recycled fillers, or combinations thereof.
[0030] In various aspects, this disclosure provides composite materials or compositions that can be used to manufacture enclosures that facilitate the transmission of microwave electromagnetic energy. The dielectric properties of these materials have been evaluated at frequencies of about 1 GHz and 100 GHz.
[0031] Further disclosure includes components for automotive radar sensors, such as plates, housings, or covers, molded from materials comprising crystalline or semi-crystalline polymers, amorphous polymers, and fillers, wherein the molded parts have a specific design, average thickness, microwave transmission efficiency, and transmission bandwidth. Another aspect of this disclosure includes articles of manufacture comprising molded parts made of radar-transmitting materials, such as radar sensors, cameras, and electronic control units (ECUs). Automotive radar sensors used for lane change assist, automatic parking, blind spot detection, and collision avoidance typically operate at a frequency of 24 GHz; those used for adaptive cruise control operate at a frequency of 77 GHz. Therefore, the compositions of this disclosure are applicable to the K-band, including a frequency of 24 GHz, and the W-band, including a frequency of 77 GHz.
[0032] Crystalline or semi-crystalline polymers
[0033] In various respects, the disclosed compositions may comprise at least one crystalline or semi-crystalline polyester. Crystallinity or semi-crystallineity of a polymer describes a polymer having organized or more closely packed molecular chains. Therefore, this highly organized molecular structure provides a more defined melting point. These polymers are anisotropic in the flow condition, thus exhibiting greater shrinkage in the transverse direction (rather than in the flow direction), which can sometimes lead to some dimensional instability. Different degrees of crystallinity can exist between different materials, and also between the same materials. Crystallinity can affect many properties of the polymer. Molecular weight and branching can affect crystallinity.
[0034] The at least one crystalline or semi-crystalline polyester includes polybutylene terephthalate (PBT), polycyclohexanediol terephthalate (PCT), polyethylene terephthalate (PET), polyethylene terephthalate glycol (PETG), polycyclohexanediol terephthalate glycol (PCTG), polycyclohexylene dimethyleneterephthalate acid (PCTA), copolymers thereof, or combinations thereof. In a particular aspect, the at least one crystalline or semi-crystalline polyester includes polybutylene terephthalate (PBT).
[0035] In various aspects of this disclosure, the thermoplastic resin may comprise crystalline or semi-crystalline polyesters. For example, the thermoplastic resin may comprise polyalkylene esters (polyesters), such as polyalkylene terephthalate polymers.
[0036] Polyesters have repeating units of the following formula (A):
[0037]
[0038] Wherein, T is a residue derived from terephthalic acid or its chemical equivalent, and D is a residue derived from the polymerization of ethylene glycol, butanediol, particularly 1,4-butanediol, or its chemical equivalent. Chemical equivalents of diacids include dialkyl esters, such as dimethyl esters, diaryl esters, acid anhydrides, salts, acyl chlorides, acyl bromides, etc. Chemical equivalents of ethylene glycol and butanediol include esters, such as dialkyl esters, diaryl esters, etc. In addition to units derived from terephthalic acid or its chemical equivalent, ethylene glycol, or butanediol (particularly 1,4-butanediol) or their chemical equivalents, other T and / or D units may be present in the polyester, provided that the type or number of such units does not significantly adversely affect the desired properties of the thermoplastic composition. Poly(alkylene arylates) may have a polyester structure according to formula (A), wherein T includes groups derived from aromatic dicarboxylic acid esters (salts), alicyclic dicarboxylic acids, or derivatives thereof.
[0039] Examples of particularly useful T groups include, but are not limited to, 1,2-phenylene, 1,3-phenylene, and 1,4-phenylene; 1,4-naphthylene and 1,5-naphthylene; cis- or trans-1,4-cyclohexyl; and so on. Specifically, when T is 1,4-phenylene, the poly(alkylene arylide) is poly(alkylene terephthalate). Furthermore, for poly(alkylene arylide), particularly useful alkylene groups D include, for example, ethylene, 1,4-butene, and bis(alkylene disubstituted cyclohexane), including cis- and / or trans-1,4-(cyclohexylene)methylene.
[0040] Examples of polyalkylene terephthalates include polyethylene terephthalate (PET), poly(1,4-butanediol terephthalate) (PBT), and poly(propylene terephthalate) (PPT). Poly(alkylene naphthoates) are also useful, such as polyethylene naphthalate (PEN) and polybutylene naphthalate (PBN). A useful poly(cycloalkylene diester) is poly(cyclohexanediol terephthalate) (PCT). Combinations comprising at least one of the above-mentioned polyesters may also be used.
[0041] Copolymers containing repeating alkylene terephthalate ester units and other ester groups can also be useful. Useful ester units may include different alkylene terephthalate units, which may exist as individual units or as blocks of poly(alkylene terephthalate) in the polymer chain. Specific examples of such copolymers include poly(cyclohexanedimethyl terephthalate)-co-poly(ethylene terephthalate), abbreviated PETG, wherein the polymer contains greater than or equal to 50 mol% poly(ethylene terephthalate), and abbreviated PCTG, wherein the polymer contains greater than 50 mol% poly(1,4-cyclohexanedimethyl terephthalate). Poly(cycloalkylene diesters) may also include poly(alkylene cyclohexanedicarboxylate). A specific example is poly(1,4-cyclohexanedicarboxylate 1,4-cyclohexanedicarboxylate) (PCCD), which has repeating units of formula (B):
[0042]
[0043] Wherein, as described using formula (A), R 2 It is a 1,4-cyclohexanedimethyl group derived from 1,4-cyclohexanediethanol, and T is a cyclohexane ring derived from cyclohexanedicarboxylic acid ester or its chemical equivalent, and may contain cis isomers, trans isomers or combinations containing at least one of the aforementioned isomers.
[0044] On the other hand, the composition may further comprise poly(1,4-butylene terephthalate) or "PBT" resin. PBT can be obtained by polymerizing a glycol component and an acid or ester component, wherein at least 70 mol%, preferably at least 80 mol%, of the glycol component is composed of tetramethylene glycol, and at least 70 mol%, preferably at least 80 mol%, of the acid or ester component is composed of terephthalic acid and / or its derivatives forming polyesters. Commercial examples of PBT include those from SABIC. TM Manufactured under the trade name VALOX TM 315, VALOX TM 195 and VALOX TM 176. Those available have an intrinsic viscosity of 0.1 dL / g to about 2.0 dL / g (or 0.1 dL / g to 2 dL / g) measured at 23°C to 30°C in a 60:40 phenol / tetrachloroethane mixture or similar solvent. In one aspect, the intrinsic viscosity of the PBT resin is 0.1 dL / g to 1.4 dL / g (or about 0.1 dL / g to about 1.4 dL / g), particularly 0.4 dL / g to 1.4 dL / g (or about 0.4 dL / g to about 1.4 dL / g).
[0045] In some aspects, the refractive index of the crystalline or semi-crystalline polyester may be less than the refractive index of the reinforcing filler present in the composition. As a specific example, when glass filler is used as the reinforcing filler, the refractive index of the crystalline or semi-crystalline polyester may be less than the refractive index of the glass. The refractive index of the crystalline or semi-crystalline polyester may be at least 1%, at least 2%, at least 5%, at least 10%, at least 15%, or at least 20% lower than the refractive index of the glass, glass filler, or glass fiber filler. The amorphous resin may have a higher refractive index than glass. In some aspects, the refractive index of the amorphous resin may be greater than 1.5, or greater than 1.55, or greater than 1.6.
[0046] As described herein, the composition may contain about 10% by weight to about 87% by weight of crystalline or semi-crystalline polyester. In other examples, the composition may comprise about 50% to about 80% by weight of crystalline or semi-crystalline polyester, about 45% to about 79% by weight of crystalline or semi-crystalline polyester, about 35% to about 80% by weight of crystalline or semi-crystalline polyester, about 45% to about 65% by weight of crystalline or semi-crystalline polyester, about 40% to about 70% by weight of crystalline or semi-crystalline polyester, or about 50% to about 97% by weight of crystalline or semi-crystalline polyester, or about 40% to about 97% by weight of crystalline or semi-crystalline polyester, or about 55% to about 97% by weight of crystalline or semi-crystalline polyester, or about 60% to about 97% by weight of crystalline or semi-crystalline polyester, or about 70% to about 97% by weight of crystalline or semi-crystalline polyester, or about 40% to about 95% by weight of crystalline or semi-crystalline polyester, or about 55% to about 95% by weight of crystalline or semi-crystalline polyester, or about 60% to about 95% by weight of crystalline or semi-crystalline polyester.
[0047] Amorphous resin
[0048] In one aspect, the thermoplastic composition may comprise a combination of at least one crystalline or semi-crystalline polyester and an amorphous resin. An amorphous polymer resin can describe a polymer resin having a randomly ordered molecular structure and may lack a discrete melting point. Such an amorphous material can gradually soften with increasing temperature. The amorphous resin is typically categorized according to its glass transition temperature T. g To characterize them. Crystalline polymers and polymers that are semi-crystalline to some extent exhibit organized and closely packed molecular chains, while the polymer chains of amorphous plastics are more unorganized.
[0049] The composition may contain about 3% to about 45% by weight of amorphous resin. The composition may contain about 4% to about 40% by weight of amorphous resin, or about 5% to about 47% by weight of amorphous resin, or about 3% to about 47% by weight of amorphous resin, or about 8% to about 40% by weight of amorphous resin, or about 8% to about 45% by weight of amorphous resin, or about 3% to about 41% by weight of amorphous resin, or about 3% to about 50% by weight of amorphous resin, or about 60% to about 95% by weight of amorphous resin.
[0050] In some respects, the refractive index of the amorphous resin may be greater than that of the reinforcing filler present in the composition. As a specific example, when glass filler is used as the reinforcing filler, the refractive index of the amorphous resin may be higher than that of the glass. The refractive index of the amorphous resin may be at least 1%, at least 2%, at least 5%, at least 10%, at least 15%, or at least 20% greater than that of the glass, glass filler, or glass fiber filler. The amorphous resin may have a higher refractive index than glass. In some respects, the refractive index of the amorphous resin may be greater than 1.5, or greater than 1.55, or greater than 1.6.
[0051] The amorphous resin may include polyetherimide (PEI), copolymer PEI, polycarbonate, copolymer polycarbonate, polyphenylene ether (PPE), copolymer PPE, polyphenylene oxide (PPO), or combinations thereof.
[0052] In some aspects, the loss factor value of the amorphous resin may be less than that of the crystalline or semi-crystalline polymer in the composition. The amorphous resin may exhibit a loss factor that is at least 1%, at least 2%, at least 5%, at least 10%, at least 15%, or at least 20% smaller than that of the crystalline or semi-crystalline polyester. In some aspects, the amorphous resin may exhibit a loss factor below 0.01 or below 0.005.
[0053] The amorphous resin may include polycarbonate, polycarbonate copolymer (e.g., polycarbonate copolymer DMX), polyphenylene ether (PPE), PPE copolymer, polyphenylene oxide (PPO), polyetherimide (PEI), PEI copolymer, or combinations thereof.
[0054] In other respects, the thermoplastic resin may include an amorphous resin, such as a polycarbonate polymer. Polycarbonate may include any polycarbonate material or mixture of materials, such as that described in U.S. Patent No. 7,786,246, the entire patent of which is incorporated herein by reference for the particular purpose of disclosing various polycarbonate compositions and methods. The term polycarbonate may be further defined as a component having repeating structural units of formula (1):
[0055]
[0056] Where R 1 At least 60% of the total number of functional groups are aromatic organic groups, with the remainder being aliphatic, alicyclic, or aromatic groups. On the other hand, each R... 1 It is an aromatic organic group, more preferably a group of formula (2):
[0057] —A 1 —Y 1 —A 2 ─ (2),
[0058] Where A 1 and A 2 Each of them is a monocyclic divalent aryl group, and Y 1 It is a bridging group having one or two atoms that separate A1 from A2. In different respects, one atom will separate A... 1 With A 2 Separation. For example, this type of group includes, but is not limited to, the following groups: ─O─, ─S─, ─S(O)─, ─S(O2)─, ─C(O)─, methylene, cyclohexyl-methylene, 2-[2.2.1]-bicycloheptene, ethylene, isopropylene, neopentylene, cyclohexylene, cyclopentadienyl, cyclododecyl, and adamantylene. Bridging group Y 1 Preferably, it contains a hydrocarbon group or a saturated hydrocarbon group, such as methylene, cyclohexylene, or isopropylene.
[0059] In various further aspects, the terms "polycarbonate" and "polycarbonate resin" as used herein further include homopolymers, polycarbonates comprising different R... 1 Copolymers (referred to herein as “copolycarbonates”), copolymers comprising carbonate units and other types of polymer units (e.g., ester units, polysiloxane units), and combinations comprising at least one of homopolymers and copolycarbonates. As used herein, “combination” includes blends, mixtures, alloys, reaction products, etc.
[0060] In a specific instance, the amorphous resin may comprise a polycarbonate copolymer, DMX. DMX describes a dimethyl bisphenol cyclohexane (DMBPC)-co-PBA polycarbonate according to the following formula:
[0061]
[0062] The amorphous resin may contain polyphenylene oxide (“poly(p-phenylene oxide”). PPO can describe a polymer containing an optionally substituted benzene ring linked by oxygen (O) and can be used interchangeably with poly(p-phenylene ether) or poly(2,6-dimethylp-phenylene oxide). Poly(p-phenylene oxide) is contained in itself or may be blended with other polymers, including but not limited to polystyrene, high-impact styrene-butadiene copolymers, and / or polyamides. Siloxane-PPO copolymers (or PPO-siloxane copolymers) may be used in various aspects of the invention. The addition of siloxane building blocks can provide additional characteristics to PPO, such as flame retardancy, low smoke, and high impact strength.
[0063] The amorphous resin may include polyetherimide. Polyetherimide (“PEI”) is a resin with a glass transition temperature (“T”). g Amorphous, transparent, high-performance polymers with a temperature greater than 180°C. In one aspect, polyetherimides may comprise polyetherimide homopolymers (e.g., polyetherimide sulfone) and polyetherimide copolymers. Polyetherimides may be selected from (i) polyetherimide homopolymers, such as polyetherimides, (ii) polyetheramide copolymers, and (iii) combinations thereof. Polyetherimides are known polymers and are marketed by SABIC under the trade name ULTEM. TM EXTEM TM and SILTEM TM Sale.
[0064] In one respect, polyetherimide can be of formula (1):
[0065]
[0066] Where a is greater than 1, for example, 10 to 1000 or greater, or more specifically 10 to 500.
[0067] In formula (1), group V is a tetravalent linking group containing an ether group (“polyetherimide” as used herein) or a combination of an ether group and an aryl sulfone group (“polyetherimide sulfone”). Such linking groups include, but are not limited to: (a) substituted or unsubstituted, saturated, unsaturated, or aromatic monocyclic and polycyclic groups having 5 to 50 carbon atoms, optionally substituted with an ether group, an aryl sulfone group, or a combination of an ether group and an aryl sulfone group; and (b) substituted or unsubstituted, linear or branched, saturated or unsaturated alkyl groups having 1 to 30 carbon atoms, and the alkyl group is optionally substituted with an ether group or a combination of an ether group, an aryl sulfone group, and an aryl sulfone group; or a combination including at least one of the above. Suitable additional substituents include, but are not limited to, ethers, amides, esters, and combinations containing at least one of the aforementioned groups.
[0068] The R group in formula (1) includes, but is not limited to, substituted or unsubstituted divalent organic groups, such as: (a) aromatic hydrocarbon groups having 6 to 20 carbon atoms and their halogenated derivatives; (b) linear or branched alkylene groups having 2 to 20 carbon atoms; (c) cycloalkylene groups having 3 to 20 carbon atoms; or (d) divalent groups of formula (2).
[0069]
[0070] Q1 includes, but is not limited to, divalent moieties such as -O-, -S-, -C(O)-, -SO2-, -SO-, -CyH2y- (y being an integer from 1 to 5), and their halogenated derivatives, including perfluoroalkylene groups.
[0071] In a further aspect, the thermoplastic composition may comprise recycled thermoplastics, such as post-consumer or post-industrial recycled thermoplastic resins (collectively referred to herein as “PCR”). More specifically, the composition may comprise recycled polyester resins. As used herein, the terms “post-consumer recycled PET,” or “recycled PET,” or “post-industrial recycled PET” refer to recycled PET containing at least one impurity not present in the corresponding, substantially similar, or identical virgin PET. The PET may be recycled from post-consumer sources, including but not limited to household appliance waste such as televisions, air conditioners, washing machines, refrigerators, etc. Regardless of the source, the recycled PET component may be similar to or even identical to those virgin plastic components, referred to as impact modifier components, which are typically used to manufacture impact-modified thermoplastic blends. However, a key difference between the virgin plastic components and the recycled plastics used in the compositions of this invention is the presence of at least one impurity not present in the virgin material. For example, one or more additives typically used to manufacture impact-modified thermoplastics may be present as impurities. Other impurities may include processing residues such as lubricants, mold release agents, antistatic agents, stabilizers, light stabilizers, flame retardants, and metals (such as iron, aluminum, and copper). Furthermore, impurities may include polyurethane particles that cannot be completely removed during recycling.
[0072] Reinforced packing
[0073] In all respects, the composition comprises reinforcing fillers. Suitable reinforcing filler components may include, for example, mica, clay, feldspar, quartz, quartzite, perlite, diatomite, diatomaceous earth, aluminosilicate (mullite), synthetic calcium silicate, fused silica, fumed silica, sand, boron nitride powder, borosilicate powder, calcium sulfate, calcium carbonate (such as chalk, limestone, marble, and synthetic precipitated calcium carbonate), talc (including fibrous, modular, acicular, and flaky talc), wollastonite, hollow or solid glass beads, silicate beads, hollow microspheres, aluminosilicates or armospheres, kaolin, silicon carbide whiskers, alumina, boron carbide, iron, nickel or copper, continuous and chopped carbon. The filler may contain fibers or glass fibers, molybdenum sulfide, zinc sulfide, barium titanate, barium ferrite, barium sulfate, barite, titanium dioxide (TiO2), alumina, magnesium oxide, granular or fibrous aluminum, bronze, zinc, copper or nickel, glass flakes, sheet silicon carbide, sheet aluminum diboride, sheet aluminum, steel flakes, natural fillers (such as wood flour, fibrous cellulose, cotton, sisal, jute, starch, lignin, peanut shells or rice husks), reinforcing organic fiber fillers (such as polyetherketone, polyimide, polybenzoxazole, poly(phenylene sulfide), polyester, polyethylene, aromatic polyamide, aromatic polyimide, polyetherimide, polytetrafluoroethylene and poly(vinyl alcohol)), and combinations comprising at least one of the aforementioned fillers or reinforcing agents. The filler and reinforcing agent may be coated with a metallic layer to promote conductivity, or surface-treated with, for example, silane to improve adhesion and dispersibility with the polymer matrix. In each respect, the refractive index of the selected reinforcing filler may be lower than that of the amorphous resin and / or higher than that of the crystalline or semi-crystalline polymer used in this disclosure.
[0074] In certain aspects, suitable reinforcing fillers include glass, such as glass fibers. In some instances, the glass fibers may be selected from E-glass, S-glass, AR-glass, T-glass, D-glass, R-glass, and combinations thereof. In some instances, the glass fibers may include E-glass (modulus less than 85 GPa), S-glass (modulus greater than 85 GPa), low dk glass (dk less than 5 or df less than 0.002, or a composition containing at least 90% silica and boron oxide) or combinations thereof.
[0075] E-glass can refer to glass fiber with a tensile modulus of 70-85 GPa and a tensile strength of 2-4 GPa. E-glass can also refer to glass fiber containing 52-62 wt% silica, 12-16 wt% alumina, 16-25 wt% calcium oxide, 0-10 wt% boron oxide, 0-5 wt% magnesium oxide and 0-5 wt% other components.
[0076] S-glass can refer to glass fibers with a tensile modulus greater than 85 GPa and a tensile strength greater than 4 GPa. S-glass can also refer to glass fibers containing 57-70 wt% silica, 18-30 wt% alumina, 0-10 wt% calcium oxide, 0-5 wt% boron oxide, 7-15 wt% magnesium oxide and 0-5 wt% other components.
[0077] Low-Dk glass can refer to glass fibers that, when measured according to the resonant cavity method, have a dielectric constant of less than 5 and / or a loss factor of less than 0.002 at frequencies from 1 GHz to 100 GHz (or 1 MHz to 100 GHz, or approximately 1-20 GHz, 1-25 GHz, 1-100 GHz, 50-100 GHz, or 70-90 GHz). Dielectric properties including Dk and Df can be measured according to any suitable method. Depending on the aspect, such dielectric properties can be measured according to the resonant cavity method, in which a hollow metal cell is used to measure the properties at microwave frequencies. Low-Dk glass can also refer to glass fibers containing at least 90% a combination of silicon dioxide and boron oxide.
[0078] The glass fibers used in the selected aspects of this disclosure may be surface-treated with a surface treatment agent containing a coupling agent to improve adhesion to the polymer base resin. Suitable coupling agents may include, but are not limited to, silane-based coupling agents, titanate-based coupling agents, or mixtures thereof. Suitable silane-based coupling agents include aminosilanes, epoxysilanes, amidesilanes, azidesilanes, and acryliclsilanes. Organometallic coupling agents, such as titanium- or zirconium-based organometallic compounds, may also be used.
[0079] Glass fibers can have various shapes. Glass fibers can include ground or chopped glass fibers. Glass fillers can be in the form of whiskers or flakes. In other instances, glass fibers can be short or long. Low-dielectric-constant glass fibers with a length of about 4 mm or longer are called long fibers, and fibers shorter than that are called short fibers. In one aspect, the diameter of the glass fiber can be about 10 μm.
[0080] The glass fibers may have a circular cross-section, a non-circular cross-section, or a combination thereof. The axial ratio of the non-circular cross-section may be in the range of 1.5 to 8, or more specifically, in the range of 3 to 5. In another aspect, the diameter of the glass fibers may be from about 1 μm to about 15 μm. More specifically, the diameter of the glass fibers may be from about 4 μm to about 10 μm.
[0081] In some aspects, the composition may contain about 10% to about 70% by weight of reinforcing filler, based on the total weight of the polymer composition. In other examples, the composition may contain about 10% to about 69% by weight of reinforcing filler. The composition may contain about 8% to about 70% by weight of reinforcing filler, or about 8% to about 69% by weight of reinforcing filler, or about 10% to about 65% by weight of reinforcing filler, or about 8% to about 65% by weight of reinforcing filler, or about 10% to about 68% by weight of reinforcing filler, such as the disclosed glass fiber.
[0082] Impact modifier
[0083] In other aspects of this disclosure, the composition may include a rubber impact modifier. The rubber impact modifier may be a polymeric material capable of substantially recovering its shape and size after force removal at room temperature. However, the glass transition temperature of the rubber impact modifier should generally be below 0°C. In some aspects, the glass transition temperature (Tg) is... g It can be below -5℃, -10℃, and -15℃, where T g Lower temperatures below -30°C typically provide better performance. Representative rubber impact modifiers may include, for example, functionalized polyolefin-ethylene-acrylate terpolymers, such as ethylene-acrylate-maleic anhydride (MAH) or glycidyl methacrylate (GMA). The functionalized rubber polymer may optionally include repeating units derived from anhydride-containing monomers (e.g., maleic anhydride) in its backbone. Alternatively, the functionalized rubber polymer may include an anhydride moiety grafted onto the polymer in a post-polymerization step.
[0084] Other impact modifiers may include styrene-butadiene-styrene (SBS), styrene-butadiene rubber (SBR), styrene-ethylene-butadiene-styrene (SEBS), styrene-ethylene-propylene-styrene (SEPS), ABS (acrylonitrile-butadiene-styrene), acrylonitrile-ethylene-propylene-diene-styrene (AES), styrene-isoprene-styrene (SIS), methyl methacrylate-butadiene-styrene (MBS), and styrene-acrylonitrile (SAN). An example of a SEBS impact modifier is high-flow SEBS, with a melt flow index greater than 3 g / 10 min at 230°C / 5 kg. In some instances, the composition may comprise an impact modifier or a mixture of impact modifiers selected from polyolefin-acrylates, ethylene-glycidyl methacrylate, ethylene-methyl acrylate-glycidyl methacrylate, ethylene-acrylate copolymers, styrene-butadiene-styrene (SBS), styrene-ethylene / 1-butene-styrene block copolymers (SEBS), and styrene-ethylene-propylene-styrene (SEPS).
[0085] The impact modifier may be included in the composition in amounts of 0 to about 10 wt% or 0.01 to about 10 wt%, based on the total composition. For example, the impact modifier may be present in amounts of 0.01-5 wt%, 7-20 wt%, 8-16 wt%, 9-15 wt%, or 9-12 wt%, for example, in amounts of about 5 wt%, about 6 wt%, about 7 wt%, about 8 wt%, about 9 wt%, about 10 wt%, about 11 wt%, about 12 wt%, about 13 wt%, about 14 wt%, about 15 wt%, about 16 wt%, about 17 wt%, about 18 wt%, about 19 wt%, about 20 wt%, about 21 wt%, about 22 wt%, about 23 wt%, about 24 wt%, or about 25 wt%.
[0086] additive
[0087] The disclosed thermoplastic compositions may contain one or more additives conventionally used in the manufacture of molded thermoplastic parts, provided that the optional additives do not adversely affect the desired properties of the resulting composition. Mixtures of optional additives may also be used. Such additives may be mixed at appropriate times during the mixing of the components used to form the composition mixture. Exemplary additives may include ultraviolet agents, ultraviolet stabilizers, heat stabilizers, antistatic agents, antimicrobial agents, anti-drip agents, radiation stabilizers, pigments, dyes, fibers, fillers, plasticizers, fibers, flame retardants, antioxidants, lubricants, wood, glass, metals, colorants, and combinations thereof.
[0088] According to certain aspects, even with a high filler content (e.g., a filler content greater than 30% by weight of the total polymer composition), the polymer composition can maintain its mechanical and dielectric properties.
[0089] The compositions disclosed herein may include one or more additional fillers. Fillers may be selected to impart additional impact strength and / or provide additional properties, which may be based on the properties of the ultimately selected polymer composition. In some aspects, fillers may include inorganic materials, such as clay, titanium dioxide, asbestos fibers, silicate and silica powders, boron powder, calcium carbonate, talc, kaolin, sulfides, barium compounds, metals and metal oxides, wollastonite, glass beads, glass fibers, sheet fillers, fibrous fillers, natural fillers and reinforcing agents, as well as reinforcing organic fiber fillers.
[0090] In some respects, the composition may contain glass fiber filler.
[0091] Suitable fillers or reinforcing agents may include, for example, mica, clay, feldspar, quartz, quartzite, perlite, diatomite, diatomaceous earth, aluminosilicate (mullite), synthetic calcium silicate, fused silica, fumed silica, sand, boron nitride powder, borosilicate powder, calcium sulfate, calcium carbonate (such as chalk, limestone, marble, and synthetic precipitated calcium carbonate), talc (including fibrous, modular, acicular, and platy talc), wollastonite, hollow or solid glass beads, silicate beads, hollow microspheres, aluminosilicates or (armospheres), kaolin, silicon carbide whiskers, alumina, boron carbide, iron, nickel or copper, continuous and chopped carbon fibers, or glass. The composition includes fibers, molybdenum sulfide, zinc sulfide, barium titanate, barium ferrite, barium sulfate, barite, titanium dioxide, alumina, magnesium oxide, granular or fibrous aluminum, bronze, zinc, copper or nickel, glass flakes, flake silicon carbide, flake aluminum diboride, flake aluminum, steel flakes, natural fillers (such as wood flour, fibrous cellulose, cotton, sisal, jute, starch, lignin, peanut shells or rice husks), reinforcing organic fiber fillers (such as poly(etherketone), polyimide, polybenzoxazole, poly(phenylene sulfide), polyester, polyethylene, aromatic polyamide, aromatic polyimide, polyetherimide, polytetrafluoroethylene and poly(vinyl alcohol)), and combinations containing at least one of the aforementioned fillers or reinforcing agents. The filler and reinforcing agent may be coated or surface-treated, for example, with silane to improve adhesion and dispersibility with the polymer matrix. The amount of filler is typically from 1 to 200 parts by weight, based on 100 parts by weight of the total composition.
[0092] In some aspects, the thermoplastic composition may contain synergists. In various examples, fillers may be used as flame-retardant synergists. When added to a flame-retardant composition, the synergist helps improve flame-retardant properties compared to a control composition containing the same amount of all the same components except the synergist. Examples of mineral fillers that can be used as synergists include mica, talc, calcium carbonate, dolomite, wollastonite, barium sulfate, silica, kaolin, feldspar, barite, etc., or combinations containing at least one of the aforementioned mineral fillers. Metallic synergists, such as antimony oxide, may also be used with the flame retardant. In one example, the synergist may include magnesium hydroxide and phosphoric acid. The average particle size of the mineral filler may be from about 0.1 to about 20 micrometers, particularly from about 0.5 to about 10 micrometers, and more particularly from about 1 to about 3 micrometers.
[0093] The thermoplastic composition may also contain antioxidants. Antioxidants may include primary or secondary antioxidants. For example, antioxidants may include organic phosphites such as tris(nonylphenyl) phosphite, tris(2,4-di-tert-butylphenyl) phosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, distearate pentaerythritol diphosphite, etc.; alkylated monophenols or polyphenols; alkylation products of polyphenols and dienes, such as tetra[methylene(3,5-di-tert-butyl-4-hydroxycinnamate)]methane, etc.; butylation products of p-cresol or dicyclopentadiene; alkylated hydroquinones; hydroxylated thiodiphenyl ethers; alkylene bisphenols; benzyl compounds; β-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid with a monohydroxy or polyhydroxy group. Esters of alkyl alcohols; esters of β-(5-tert-butyl-4-hydroxy-3-methylphenyl)-propionic acid with monohydroxy or polyhydroxy alcohols; esters of thioalkyl or thioaryl compounds, such as distearylthiopropionate, dilaurylthiopropionate, ditridecylthiodipropionate, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, pentaerythritolyl-tetra[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, etc.; amides of β-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, etc., or combinations comprising at least one of the aforementioned antioxidants. The amount of antioxidant is typically 0.01 to 0.5 parts by weight, based on 100 parts by weight of total composition (excluding any fillers).
[0094] In various respects, the thermoplastic composition may include a release agent. Exemplary release agents may include, for example, metal stearates, stearyl stearates, pentaerythritol tetrastearates, beeswax, montan wax, paraffin wax, etc., or combinations comprising at least one of the foregoing release agents. The amount of release agent is typically from about 0.1 to about 1.0 parts by weight, based on 100 parts by weight of the total composition (excluding any fillers).
[0095] In one aspect, the thermoplastic composition may include a heat stabilizer. As examples, the heat stabilizer may include, for instance, organic phosphites such as triphenyl phosphite, tri-(2,6-dimethylphenyl) phosphite, tri-(mixed monononylphenyl and dinonylphenyl) phosphite, etc.; phosphonates (such as dimethylphenylphosphonate, etc.), phosphate esters (such as trimethyl phosphate, etc.), or combinations including at least one of the aforementioned heat stabilizers. The amount of heat stabilizer is typically 0.01 to 0.5 parts by weight, based on 100 parts by weight of the total composition (excluding any fillers).
[0096] In other respects, a light stabilizer may be present in the thermoplastic composition. Exemplary light stabilizers may include, for example, benzotriazoles, such as 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, and 2-hydroxy-4-n-octyloxybenzophenone, or combinations comprising at least one of the foregoing light stabilizers. The amount of light stabilizer is typically from about 0.1 to about 1.0 parts by weight, based on 100 parts by weight of the total composition (excluding any fillers).
[0097] The thermoplastic composition may also contain a plasticizer. For example, the plasticizer may include phthalates such as dioctyl-4,5-epoxy-hexahydrophthalate, tri-(octyloxycarbonylethyl)isocyanurate, tristearate, epoxidized soybean oil, etc., or a combination including at least one of the aforementioned plasticizers. The amount of plasticizer is typically from about 0.5 to about 3.0 parts by weight, based on 100 parts by weight of the total composition (excluding any fillers).
[0098] Ultraviolet (UV) absorbers may also be present in the disclosed thermoplastic compositions. Exemplary UV absorbers may include, for example, hydroxybenzophenone; hydroxybenzotriazole; hydroxybenzotriazine; cyanoacrylate; N,N'-oxanilides; benzoxazinone; 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)-phenol (CYASORB) TM 5411); 2-Hydroxy-4-n-Octyloxybenzophenone (CYASORB) TM 531); 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]-5-(octyloxy)-phenol (CYASORB) TM 1164); 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazin-4-one)(CYASORB TM UV-3638); 1,3-bis[(2-cyano-3,3-diphenylacryloyl)oxy]-2,2-bis[[(2-cyano-3,3-diphenylacryloyl)oxy]methyl]propane (UVINUL) TM 3030); 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazin-4-one); 1,3-bis[(2-cyano-3,3-diphenylacryloyl)oxy]-2,2-bis[[(2-cyano-3,3-diphenylacryloyl)oxy]methyl]propane; nanoscale inorganic materials, such as titanium oxide, cerium oxide, and zinc oxide, all with particle sizes less than 100 nanometers; etc., or a combination including at least one of the aforementioned UV absorbers. The amount of UV absorber is typically 0.01 to 3.0 parts by weight, based on 100 parts by weight of total composition (excluding any fillers).
[0099] The thermoplastic composition may further comprise a lubricant. For example, the lubricant may comprise, for instance, fatty acid esters, such as alkyl stearyl esters, like methyl stearate; mixtures of methyl stearate with hydrophilic and hydrophobic surfactants (including polyethylene glycol polymers, polypropylene glycol polymers, and copolymers thereof), such as methyl stearate with a polyethylene glycol-polypropylene glycol copolymer in a suitable solvent; or combinations comprising at least one of the aforementioned lubricants. The amount of lubricant is typically from about 0.1 to about 5 parts by weight, based on 100 parts by weight of the total composition (excluding any fillers).
[0100] Anti-drip agents can also be used in this composition, such as fluoropolymers that form fibrils or do not, such as polytetrafluoroethylene (PTFE). The anti-drip agent can be encapsulated by a rigid copolymer (e.g., styrene-acrylonitrile copolymer (SAN)). PTFE encapsulated in SAN is referred to as TSAN. In one example, TSAN may contain 50% by weight of PTFE and 50% by weight of SAN, based on the total weight of the encapsulated fluoropolymer. SAN may contain, for example, 75% by weight of styrene and 25% by weight of acrylonitrile, based on the total weight of the copolymer. The amount of anti-drip agent is typically from 0.1 to 10 parts by weight, based on 100 parts by weight of the total composition (excluding any fillers).
[0101] As an example, the disclosed composition may include an impact modifier. The impact modifier may be a chemically reactive impact modifier. By definition, a chemically reactive impact modifier may have at least one reactive group, thereby improving the impact properties (expressed as Izod impact value) of the composition when the impact modifier is added to the polymer composition. In some examples, the chemically reactive impact modifier may be an ethylene copolymer having reactive functional groups selected from, but not limited to, acid anhydrides, carboxyl groups, hydroxyl groups, and epoxy resins.
[0102] The composition may contain one colorant or a mixture of colorants, said colorant being selected from organic dyes and inorganic colorants. The inorganic colorant may contain one or more inorganic elements selected from carbon, titanium, zinc, sodium, magnesium, calcium, and aluminum.
[0103] Properties and products
[0104] In some respects, the disclosed compositions may exhibit certain dielectric, warpage, and light transmittance properties. When measured according to the resonant cavity method, at frequencies of 1-90 GHz, molded articles or plaques containing the composition may exhibit a loss factor (Df) of about 0.001 to about 2. The composition may exhibit a higher transmittance than that observed by the UV-VIS-IR method for reference compositions in the absence of amorphous resin.
[0105] Sheets molded from the disclosed compositions may exhibit warpage properties. Warpage can be defined as the degree of dimensional deformation of the molded product after ejection from the mold at the end of the injection molding process. With increasing focus on thin-walled products, control of dimensional stability is becoming increasingly important. For example, compared to a control composition not containing amorphous polymers, molded samples may exhibit lower warpage values in terms of mean and standard deviation determined using the methods described above. In other respects, warpage can be determined by observing (visually or quantitatively) the extent of peeling from a plane on which the molded part containing the composition is placed. This composition may exhibit lower warpage than observed in reference compositions not containing amorphous polymer resins.
[0106] Plates molded from the disclosed compositions exhibit light transmittance properties. With increasing attention on laser-welded components for radomes, the demand for high-transmittance materials is also growing. The transmittance percentages described herein can be measured using UV-VIS-IR transmittance methods. For example, compared to a reference composition that does not contain amorphous polymers, the molded samples exhibit higher transmittance values at wavelengths of 900–1100 nm (the range for laser applications).
[0107] In various aspects, this disclosure relates to articles comprising the compositions described herein. These compositions can be molded into useful shaped articles by various methods, such as injection molding, extrusion, rotational molding, blow molding, and thermoforming. The compositions can be used to manufacture articles requiring materials with good flowability, good smoothness, good microwave transmittance, and good light transmittance properties. The advantageous properties of the compositions disclosed herein make them suitable for a range of applications. In various aspects, this disclosure provides materials that can be used to manufacture housings that are permeable to microwave electromagnetic energy. This document further discloses radar sensor components (e.g., plates, housings, covers) made from these materials, and articles (sensors, cameras, ECUs) made from these components.
[0108] Manufacturing method
[0109] This invention also relates to methods for preparing thermoplastic compositions. One or any of the aforementioned components described herein may first be dry-mixed with each other, or with any combination of the aforementioned components, and then fed into an extruder from one or more feeders, or individually fed into an extruder from one or more feeders. Fillers used in this disclosure may also first be processed into masterbatch and then fed into the extruder. Components may be fed into the extruder from a throat hopper or any side feeder.
[0110] The extruder used in this invention may have a single screw, multiple screws, intermeshing screws rotating in the same or opposite directions, non-intermeshing screws rotating in the same or opposite directions, reciprocating screws, pinned screws, screws with screens, pinned cylinders, rollers, plungers, helical rotors, co-kneaders, disc packaging processors, various other types of extrusion equipment, or combinations of at least one of the above.
[0111] The components may also be mixed together and then melt-blended to form a thermoplastic composition. Melt blending of the components involves the use of shear force, tensile force, compressive force, ultrasonic energy, electromagnetic energy, thermal energy, or a combination including at least one of the aforementioned forms of force or energy. If the resin is a crystalline or semi-crystalline organic polymer, the barrel temperature on the extruder during compounding may be set to a temperature at least a portion of the polymer that reaches a temperature greater than or equal to approximately the melt temperature, or if the resin is an amorphous resin, it may be set to a temperature at least a portion of the polymer that reaches a temperature greater than or equal to approximately the pour point (e.g., glass transition temperature).
[0112] If desired, the mixture containing the above components can undergo multiple mixing and forming steps. For example, the thermoplastic composition can first be extruded and formed into pellets. The pellets can then be fed into a molding machine, where they can be formed into any desired shape or product. Alternatively, the thermoplastic composition produced from a single melt mixer can be formed into sheets or strands and subjected to post-extrusion processes, such as annealing, uniaxial or biaxial orientation.
[0113] In this process, the melt temperature is kept as low as possible in some respects to avoid excessive thermal degradation of the components. In some respects, the melt temperature is maintained between about 230°C and about 350°C, but higher temperatures can be used, provided that the residence time of the resin in the processing equipment is kept relatively short. In some respects, the melt-processed composition exits the processing equipment, such as an extruder, through a small outlet orifice in a die. The resulting molten resin ply can be cooled by passing the ply through a water bath. The cooled ply can be cut into pellets for packaging and further processing.
[0114] The methods may also include processing the composition to provide a sheet of desired thickness. The sheet may be extruded, injection molded, compression molded, or injection compression molded, with a thickness between about 0.5 mm and 6 mm. Other processes may also be applied to thin thermoplastic films, including but not limited to lamination, co-extrusion, thermoforming, or hot pressing. In these respects, further layers of other materials (e.g., other thermoplastic polymer layers, metal layers, etc.) may be combined with the composition.
[0115] This invention covers various combinations of elements of the invention, such as combinations of elements from dependent claims that are subordinate to the same independent claim.
[0116] definition
[0117] It should also be understood that the terminology used herein is for descriptive purposes only and is not intended to be limiting. As used in the specification and claims, the term "comprising" may include embodiments of "consisting of" and "essentially composed of". Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Reference will be made to several terms as defined herein in this specification and the following claims. As used in this specification and the appended claims, the singular forms "a", "an", and "the" also include plural references unless the context clearly specifies otherwise. Thus, for example, reference to "thermoplastic polymer component" includes a mixture of two or more thermoplastic polymer components. As used herein, the term "combination" includes blends, mixtures, alloys, reaction products, etc.
[0118] A range may be expressed herein as a range from one value (the first value) to another value (the second value). When such a range is expressed, it includes one or both of the first and second values in some respects. Similarly, when a value is expressed as an approximation, it can be understood that a particular value forms the other side by using the antecedent “about.” It will be further understood that each endpoint of a range is significant relative to and independent of the other endpoint. It should also be understood that multiple values are disclosed herein, and each value is also disclosed herein as an “about” specific value in addition to the value itself. For example, if the value “10” is disclosed, then “about 10” is also disclosed. It should also be understood that each unit between two specific units is also disclosed. For example, if 10 and 15 are disclosed, then 11, 12, 13, and 14 are also disclosed.
[0119] As used herein, the terms “about” and “at or about” mean that the quantity or value in question may be a specified value, approximately a specified value, or substantially the same as a specified value. It is generally understood that, as used herein, unless otherwise stated or inferred, it is a variation of the indicated nominal value by ±10%. This term is intended to convey that similar values promote equivalent results or effects recounted in the claims. That is, it should be understood that quantities, dimensions, formulations, parameters, and other quantities and characteristics are not and need not be precise, but may be approximate and / or larger or smaller as required, reflecting tolerances, conversion factors, rounding, measurement errors, and other factors known to those skilled in the art. Generally, quantities, dimensions, formulations, parameters, or other quantities or characteristics are “about” or “approximately”, whether or not explicitly stated so. It should be understood that when “about” is used before a quantitative value, unless otherwise specifically stated, the parameter also includes the specific quantitative value itself.
[0120] As used herein, the terms “optional” or “optionally” mean that an event or situation described below may or may not occur, and the description includes both cases where the event or situation occurs and cases where the event or situation does not occur. For example, the phrase “optional additional process” means that additional processes may or may not be included, and the description includes both cases where additional processes are included and cases where additional processes are not included.
[0121] The components for preparing the compositions of the present invention and the compositions themselves to be used in the methods disclosed herein are disclosed. These and other materials are disclosed herein, and it should be understood that when combinations, subsets, interactions, groups, etc., of these materials are disclosed, although specific mentions of the various individual and collective combinations and arrangements of these compounds cannot be explicitly disclosed, each is specifically considered and described herein. For example, if a particular compound is disclosed and discussed, and various modifications that may be made to the multiple molecules comprising that compound are discussed, then the various combinations and arrangements of the compounds and possible modifications are specifically considered unless specifically indicated to the contrary. Thus, if a class of molecules A, B, and C and a class of molecules D, E, and F are disclosed, and an example of the combination molecule AD is disclosed, then even if each case is not described separately, it is individually and collectively encompassed, thereby implying that combinations AE, AF, BD, BE, BF, CD, CE, and CF are also disclosed. Similarly, any subsets or combinations of these are also disclosed. Thus, for example, subgroups of AE, BF, and CE are considered to be disclosed. This concept applies to all aspects of this application, including but not limited to the steps in methods of making and using the compositions of the present invention. Therefore, if various additional steps are available, it should be understood that each of these additional steps may be performed in any particular aspect or combination thereof of the methods of the present invention.
[0122] References to the parts by weight of a particular element or component in a composition or article in the specification and conclusions indicate the weight relationship between one element or component and any other element or component in the composition or article (expressed in parts by weight). Therefore, in a compound containing 2 parts by weight of component X and 5 parts by weight of component Y, X and Y are present in a weight ratio of 2:5, and this ratio applies regardless of whether the compound contains other components.
[0123] Unless otherwise stated, the weight percentage of a component is based on the total weight of the formulation or composition containing that component.
[0124] The terms “residue” and “structural unit” used to refer to components of the polymer are synonymous throughout the specification.
[0125] In one aspect, "substantially free" can mean present in a given composition or component in an amount of 0.5% by weight or less than about 0.5% by weight. In another aspect, substantially free can mean less than 0.1% by weight or less than about 0.1% by weight. In yet another aspect, substantially free can mean less than 0.01% by weight or less than about 0.01% by weight. In yet another aspect, substantially free can mean less than 100 parts per million (ppm) or less than about 100 ppm. In yet another aspect, substantially free can mean below a detectable level (if present). "Substantially free" or "free" can also mean a component that is not added to or incorporated into the composition. For example, the composition may be free of or substantially free of impact modifiers.
[0126] In this application, the conventional understanding of "crystalline," "semi-crystalline," and "amorphous" polymers is used. For example, crystalline polymers are considered to have a very high degree of crystallinity (e.g., 95-99%). Crystalline polymers are rigid and have high melting temperatures. They are less affected by solvent penetration. Semi-crystalline polymers can have both crystalline and amorphous regions. Semi-crystalline polymers combine the strength of crystalline polymers with the flexibility of amorphous polymers. Semi-crystalline polymers can be tough, capable of bending without breaking. Amorphous polymers have polymer chains with branched or irregular groups that cannot be packed together regularly enough to form crystals. The amorphous regions of a polymer consist of randomly coiled and entangled chains; they are softer and have lower melting points than crystalline and semi-crystalline polymers.
[0127] As used herein, the terms “weight percentage,” “weight % (wt%),” and “weight % (wt.%)” are used interchangeably to indicate the weight percentage of a given component based on the total weight of the composition, unless otherwise specified. That is, unless otherwise specified, all wt% values are based on the total weight of the composition. It should be understood that the sum of the weight % values of all components in the disclosed compositions or formulations is 100.
[0128] Unless otherwise provided herein, all testing standards are the most current standards in effect at the time of submission of this application.
[0129] Each material disclosed herein is commercially available, and / or its production method is known to those skilled in the art.
[0130] It should be understood that the compositions disclosed herein have certain functions. Certain structural requirements for performing the disclosed functions are disclosed herein, and it should be understood that various structures exist capable of performing the same functions associated with the disclosed structures, and these structures will generally achieve the same effects.
[0131] Various aspects of this disclosure
[0132] In various respects, the present invention relates to and includes at least the following aspects.
[0133] Aspect 1A. A thermoplastic composition comprising: (a) about 10% to about 87% by weight of at least one crystalline or semi-crystalline polymer, wherein the at least one crystalline polymer comprises a crystalline or semi-crystalline polyester; (b) about 3% to about 40% by weight of an amorphous polymer resin; and (c) about 10% to about 70% by weight of a reinforcing filler, wherein: when measured using a refractometer, the refractive index of the at least one crystalline or semi-crystalline polymer is lower than the refractive index of the reinforcing filler, the refractive index of the amorphous polymer resin is greater than the refractive index of the reinforcing filler, the combined weight percentage of all components does not exceed 100% by weight, and all weight percentages are based on the total weight of the composition, and the composition exhibits a smaller loss factor Df than that observed for a reference composition in the absence of an amorphous resin.
[0134] Aspect 1C. A thermoplastic composition comprising essentially the following: (a) about 10 wt% to about 87 wt% of at least one crystalline or semi-crystalline polymer, wherein the at least one crystalline or semi-crystalline polymer comprises a crystalline or semi-crystalline polyester; (b) about 3 wt% to about 40 wt% of an amorphous polymer resin; and (c) about 10 wt% to about 70 wt% of a reinforcing filler, wherein: when measured using a refractometer, the refractive index of the at least one crystalline or semi-crystalline polymer is lower than the refractive index of the reinforcing filler, the refractive index of the amorphous polymer resin is greater than the refractive index of the reinforcing filler, the combined weight percentage of all components does not exceed 100 wt%, and all weight percentages are based on the total weight of the composition, and the composition exhibits a smaller loss factor Df than that observed for a reference composition in the absence of an amorphous resin.
[0135] Aspect 1D. A thermoplastic composition comprising: (a) about 10% to about 87% by weight of at least one crystalline or semi-crystalline polymer, wherein the at least one crystalline or semi-crystalline polymer comprises a crystalline or semi-crystalline polyester; (b) about 3% to about 40% by weight of an amorphous polymer resin; and (c) about 10% to about 70% by weight of a reinforcing filler, wherein: when measured using a refractometer, the refractive index of the at least one crystalline or semi-crystalline polymer is lower than the refractive index of the reinforcing filler, the refractive index of the amorphous polymer resin is greater than the refractive index of the reinforcing filler, the combined weight percentage of all components does not exceed 100% by weight, and all weight percentages are based on the total weight of the composition.
[0136] Aspect 2. The thermoplastic composition according to claim 1, wherein the crystalline or semi-crystalline polyester comprises polybutylene terephthalate (PBT), polycyclohexanediol terephthalate (PCT), polyethylene terephthalate diol (PCTG), polycyclohexanediol terephthalate diol (PCTG), polycyclohexanediol terephthalate acid (PCTA), copolymers thereof, or combinations thereof.
[0137] Aspect 3. The thermoplastic composition according to claim 1, wherein the crystalline or semi-crystalline polyester comprises polybutylene terephthalate (PBT).
[0138] Aspect 4. The thermoplastic composition according to claim 1, wherein the crystalline or semi-crystalline polyester comprises recycled polybutylene terephthalate.
[0139] Aspect 5. The thermoplastic composition according to any one of claims 1 to 4, wherein the amorphous resin comprises polycarbonate, copolymer polycarbonate, dimethyl bisphenol cyclohexane (DMBPC)-co-PBA polycarbonate, polyphenylene ether (PPE), polyphenylene oxide (PPE), copolymer PPE, polyetherimide (PEI), copolymer PEI, or a combination thereof.
[0140] Aspect 6. The thermoplastic composition according to any one of claims 1 to 5, wherein the composition further comprises about 0.01% by weight to about 10% by weight of at least one impact modifier.
[0141] 7. The thermoplastic composition according to claim 6, wherein the at least one impact modifier comprises polyolefin-acrylate, ethylene-glycidyl methacrylate, ethylene-methyl acrylate-glycidyl methacrylate, ethylene-acrylate copolymer, styrene-butadiene-styrene (SBS), styrene-ethylene / 1-butene-styrene block copolymer (SEBS), or a combination thereof.
[0142] 8. The thermoplastic composition according to any one of claims 1 to 7, wherein the reinforcing filler comprises glass fiber.
[0143] Aspect 9. The thermoplastic composition according to any one of claims 1 to 8, wherein the at least one glass fiber comprises E-glass (modulus less than 85 GPa), S-glass (modulus greater than 85 GPa), low dk glass (dk less than 5, and / or df less than 0.002, and / or a composition comprising at least 90% silica and boron oxide) or a combination thereof.
[0144] Aspect 10. The thermoplastic composition according to any one of claims 1 to 9, wherein the at least one glass fiber comprises a circular cross-section, a non-circular cross-section, or a combination thereof. Aspect 11. The thermoplastic composition according to any one of claims 1 to 10, wherein the composition exhibits less warpage than observed in a reference composition lacking amorphous resin, the warpage being measured as the amount of displacement from a flat surface.
[0145] Aspect 12. The thermoplastic composition according to any one of claims 1 to 11, wherein, when measured using a UV-VIS-IR spectrometer, the composition exhibits a higher transmittance value than that observed for a reference composition in the absence of amorphous resin.
[0146] Aspect 13. The thermoplastic composition according to any one of claims 1 to 12, wherein, when measured according to the resonant cavity method, the composition exhibits a loss factor (Df) of about 0.001 to about 2 at a frequency of 1-90 GHz with a ratio of ε” to ε’.
[0147] Aspect 14. The thermoplastic composition according to any one of claims 1-13, wherein, when measured according to the resonant cavity method, the composition exhibits a loss factor (Df) of about 0.001 to about 0.02 at a frequency of 1-100 GHz, determined by the ratio of ε” to ε’.
[0148] Aspect 15. The thermoplastic composition according to any one of claims 1-14, further comprising additive materials selected from: antioxidants; colorants; release agents; dyes; flow promoters; flow modifiers; light stabilizers; lubricants; release agents; pigments; colorants, quenchers; heat stabilizers; ultraviolet (UV) absorbers; UV reflectors; UV stabilizers; epoxy chain extenders; flame retardants; and combinations thereof.
[0149] Aspect 16. The thermoplastic composition according to any one of claims 1-15, wherein the composition is a component of an automotive radar sensor.
[0150] Aspect 17. Article comprising the thermoplastic composition according to any one of claims 1-15.
[0151] Example
[0152] The following examples are provided to provide those skilled in the art with a complete disclosure and description of how to prepare and evaluate the compounds, compositions, articles, apparatus, and / or methods claimed herein, and are intended to be purely exemplary and not to limit the scope of this disclosure. Efforts have been made to ensure the accuracy of figures (e.g., quantities, temperatures, etc.), but some errors and deviations should be accounted for. Unless otherwise stated, parts are by weight, temperatures are expressed in °C or at ambient temperature, and pressures are at or near atmospheric pressure. Unless otherwise stated, percentages of a composition are expressed in % by weight. There are many variations and combinations of mixing conditions, such as component concentrations, extruder design, feed rate, screw speed, temperature, pressure, and other mixing ranges and conditions that can be used to optimize the purity and yield of the product obtained by the process. Reasonable routine experimentation is required to optimize these process conditions.
[0153] Various PBT composition samples were prepared. Examples of glass-filled PBT (30% glass fiber by weight) are shown in Table 1-1. Figure 1As shown in the figure. These formulations contain amorphous PEI resin, which has a refractive index (RI) of about 1.63 to 1.65 when observed at room temperature using a refractometer (Abbe refractometer or Metricon Model 2010 Prism Coupler) (this value is higher than the refractive index of glass or glass fiber). The control formulations include PBT with an RI of about 1.52 to 1.54, which is lower than the RI of glass.
[0154] Table 1-2 Figure 2 The observed properties, along with the corresponding test instructions and standards, are presented. Light transmittance was determined at 980 nm using a UV-VIS-IR spectrometer (Shimadzu Uv-3510). Dielectric properties were measured using the resonant cavity method. For frequencies from 1 to 20 GHz, an Agilent split resonator was used. The same method was used for frequencies from 70 to 90 GHz with alternating radio broadcast frequencies. The results in Table 2 show that the use of PEI increased light transmittance, reduced the loss factor, and decreased the warpage (in terms of both mean and standard deviation). Good mechanical properties were also observed using PEI. Figure 3 shows the light transmittance of this formulation over a wider wavelength range (250 to 2500 nm). This indicates that blending PEI with PBT significantly improves light transmittance. The light transmittance of samples prepared at different thicknesses (1–3 mm) is shown in Figure 4, establishing a consistent increase across different thicknesses.
[0155] Formulations with different types of glass fibers (i.e., low-dk glass fibers) were also prepared, and are shown in Table 2-1. Figure 5 As shown in Table 2-2, the RI of amorphous resin PEI is higher than that of low-dk glass. A control formulation containing PBT was also prepared, with a lower RI than that of low-dk glass. Figure 6 The observed properties and corresponding test standards are presented. Dielectric properties were measured using the resonant cavity method. For frequencies from 1 to 20 GHz, an Agilent resonant split instrument was used. The same method was used for frequencies from 70 to 90 GHz with alternating radio broadcast frequencies.
[0156] Warpage was measured on a molded sample disc with a diameter of 135 mm and a thickness of 1.2 mm using an internal method. The disc was placed on a flat surface, and four points (A, B, C, D) were marked equidistantly along its edge. Point D was pressed into the surface, while the remaining points were raised along the edge of the disc. The distance from each point A, B, and C to the flat surface was obtained, yielding the warpage. The mean and standard deviation of the warpages A, B, and C were calculated.
[0157] The results in Table 2-2 show that the use of PEI increased light transmittance, reduced the loss factor, and decreased the warpage (in terms of both mean and standard deviation). Good mechanical properties were also observed with the use of PEI.
[0158] Table 3-1 Figure 7 Examples of glass-filled PBT with higher proportions are given in [reference needed]. These formulations contain 50% and 60% E-glass.
[0159] The results in Table 3-2 ( Figure 8 Further evidence shows that PEI increases light transmittance, reduces the loss factor, and decreases warpage (in terms of both mean and standard deviation). Good mechanical properties were also observed using PEI. Table 4-1 ( Figure 9 Examples of glass-filled PBT with lower proportions are given in [reference needed]. These formulations used 20% E glass.
[0160] Table 4-2 Figure 10 The results also showed that amorphous PEI increased light transmittance, reduced the loss factor, and decreased the warpage (in terms of both mean and standard deviation). Good mechanical properties were also observed using PEI.
[0161] Table 5-1 Figure 11 Table 5-2 shows examples of PBT containing colorants, impact modifiers, recycled polyester, and blended types of glass fibers. Figure 12 The results showed that the use of PEI increased light transmittance, decreased the loss factor, and reduced (consistently across different formulations) warpage (in terms of both mean and standard deviation). Examples 5.1 and 5.2 demonstrated that, in the presence of dyes, light transmittance, loss factor, and warpage remained positive compared to the previous control. Example 5.3 showed that, in the presence of impact modifiers, loss factor and warpage remained improved (lower) compared to the control. Examples 5.4 and 5.5 showed that, in the presence of recycled polyesters, loss factor and warpage remained improved compared to the control. Example 5.5 further demonstrated that loss factor and warpage were also improved when using a mixture of glass fibers. Good mechanical properties were also observed in these formulations through the use of PEI.
[0162] More comparative samples were observed. Table 6-1 ( Figure 13Examples of PBT containing different second polymers are given in [reference needed]. Not all low Df polymers have the same effect. Polypropylene is the lowest df polymer among engineering plastics (Df is about 0.0001), with an RI of about 1.45-1.5 (lower than the RI of glass), but it has crystalline or semi-crystalline characteristics. Another amorphous example was also observed with amorphous polycarbonates and their copolymers.
[0163] Table 6-2 Figure 14 The results showed that the use of polypropylene in glass-filled PBT significantly reduced light transmittance and significantly increased warpage, regardless of the copolymer type of polypropylene (C6.1, C6.2). Conversely, amorphous polycarbonate, with a higher RI than glass and a lower Df than PBT, still increased light transmittance, reduced loss factor, and reduced warpage.
[0164] The above description is intended to be illustrative and not restrictive. For example, the above examples (or one or more aspects thereof) may be used in combination with each other. Other embodiments may be used, such as those used by those skilled in the art in recalling the above description. The abstract is provided to allow the reader to quickly determine the nature of the technical disclosure. It is understood that this document is not intended to interpret or limit the scope or meaning of the claims. Furthermore, in the above detailed description, various features may be grouped together to simplify the invention. This should not be construed as meaning that any unclaimed disclosed feature is essential to any claim. Rather, the subject matter of the invention may not be limited to all features of the particular embodiments disclosed. Therefore, the following claims are incorporated herein as embodiments or implementations, each claim being an independent separate implementation, and such implementations are contemplated to be combined or arranged in various ways. The scope of this disclosure should be determined by reference to the appended claims and the full scope of their equivalents.
[0165] It will be apparent to those skilled in the art that various modifications and variations may be made to this invention without departing from its scope or spirit. Other embodiments of the invention will be apparent to those skilled in the art upon consideration of the specification and practice disclosed herein. This specification and embodiments are to be considered exemplary only, and the true scope and spirit of this disclosure are indicated by the following claims.
[0166] The patentable scope of this invention is defined by the claims, but may include other instances that can be made by a person skilled in the art. Such other instances are intended to fall within the scope of the claims if they have structural elements that are indistinguishable from the wording of the claims, or if they include equivalent structural elements that are not substantially different from the wording of the claims.
Claims
1. A thermoplastic composition comprising: (a) 10% to 87% by weight of at least one crystalline or semi-crystalline polyester; (b) 15% to 40% by weight of polyetherimide resin; and (c) 10% to 70% by weight of glass fibers having a non-circular cross-section, wherein the axial ratio of the non-circular cross-section is in the range of 1.5 to 8. in When measured using a refractometer, the refractive index of the at least one crystalline or semi-crystalline polyester is lower than that of the glass fiber having a non-circular cross-section. The refractive index of the polyetherimide resin is greater than that of the glass fiber with a non-circular cross-section. The composition exhibits a smaller loss factor Df than that observed in the reference composition which does not contain polyetherimide resin. The warpage exhibited by the composition was less than that observed in a reference composition lacking polyetherimide resin, the warpage being measured as the amount of displacement from a flat surface, and The combined weight percentage of all components does not exceed 100% by weight, and all weight percentages are based on the total weight of the composition.
2. The thermoplastic composition according to claim 1, wherein, The crystalline or semi-crystalline polyesters include polybutylene terephthalate (PBT), polycyclohexanediol terephthalate (PCT), polyethylene terephthalate diol (PETG), polycyclohexanediol terephthalate diol (PCTG), polycyclohexanediol terephthalate acid (PCTA), copolymers thereof, or combinations thereof.
3. The thermoplastic composition according to claim 1, wherein, The crystalline or semi-crystalline polyester includes polybutylene terephthalate (PBT).
4. The thermoplastic composition according to claim 1, wherein, The crystalline or semi-crystalline polyester includes recycled polybutylene terephthalate.
5. The thermoplastic composition according to claim 1, wherein the composition further comprises 0.01% to 10% by weight of at least one impact modifier.
6. The thermoplastic composition according to claim 5, wherein, The at least one impact modifier includes polyolefin-acrylate, ethylene-glycidyl methacrylate, ethylene-methyl acrylate-glycidyl methacrylate, styrene-butadiene-styrene (SBS), styrene-ethylene / 1-butene-styrene block copolymer (SEBS), styrene-ethylene-propylene-styrene (SEPS), or combinations thereof.
7. The thermoplastic composition according to claim 6, wherein, The polyolefin-acrylate is selected from ethylene acrylate copolymers.
8. The thermoplastic composition according to claim 1, wherein, The glass fibers with non-circular cross-sections include E-glass, S-glass, low-dk glass fibers, or combinations thereof.
9. The thermoplastic composition according to any one of claims 1-8, wherein, When measured using a UV-VIS-IR spectrometer, the composition exhibits a higher light transmittance value than that observed for a reference composition in the absence of polyetherimide resin.
10. The thermoplastic composition according to any one of claims 1-8, wherein, When measured according to the resonant cavity method, at frequencies of 1-90 GHz... and When the ratio was measured, the composition exhibited a loss factor (Df) of 0.001 to 2.
11. The thermoplastic composition according to any one of claims 1-8, wherein, When measured according to the resonant cavity method, at frequencies of 1-100 GHz... and When the ratio was measured, the composition exhibited a loss factor (Df) of 0.001 to 0.
02.
12. The thermoplastic composition according to any one of claims 1-8, further comprising an additive material selected from: antioxidants; colorants; flow modifiers; light stabilizers; lubricants; release agents; quenchers; heat stabilizers; epoxy chain extenders; flame retardants; and combinations thereof.
13. The thermoplastic composition according to claim 12, wherein, The colorant is selected from dyes and pigments.
14. The thermoplastic composition according to claim 12, wherein, The flow modifier is selected from flow promoters.
15. The thermoplastic composition according to claim 12, wherein, The light stabilizer is selected from UV stabilizers.
16. The thermoplastic composition according to claim 15, wherein, The UV stabilizer is selected from ultraviolet (UV) absorbers and UV reflectors.
Citation Information
Patent Citations
Isosorbide-based polycarbonates, method of making, and articles formed therefrom
US7786246B2
Reinforced thermoplastic compound with chemical resistance
CN106459564A
Filler reinforced thermoplastic compositions with improved bonding strength
CN106536625A
High-strength, high-gloss and low-warpage PBT composite material and preparation method and application thereof
CN111073226A
Processing aids for filler dispersion and uses thereof
WO2019116267A1
